The Association Between Corporate Risk Disclosure and Firm Performance in Emerging Country – The Case of Egypt - Razek, Marwa Abdel (Journal of Empirical Studies, 2014)
The aim of this paper is to investigate the association between corporate risk disclosure and firm performance (ROA, ROE, and ESP), Using SPSS statistical, results show that there is an insignificant association between liquidity risk, interest rate risk, credit risk, exchange rate and firm profitability. This study is restricted to examine one year annual report 2013, exclude financial sector due to their specific law and rules and sample size on the other hand, this research paper is limited to investigating the association between risk disclosure mainly financial risk, liquidity risk and profitability